The Influence of Government Spending on the Achievement of Human Development Index in East Java - Fadilah, Anisa; Ananda, Candra Fajri; Kaluge, David (Universitas Negeri Malang, 2018)
This study was intendedto: 1)investigatethe influence of government spending on education index, health index and income index of regional governments in East Java; 2) investigate the influence of government spendingon the development of under-developed and developed regionsin East Java; 3) investigatethe influenceof government spendingon the development of citiesand districtsin East Java. This study employed a quantitative approach using the Fixed Effect Model and Random Effect Model as the panel data analysis method. There were 38 cities and districts used as the analysis units during 2010-2015. The result of this study shows that government spending on education, health, and economic has a positive and significant influence on every component of human development index. In addition, government spending on infrastructure has a significant influence on the education index and income index yet it does not significantly influence the health index. Furthermore, this study shows different results on the influence of government spending on under-developed and developed regions.Keywords: Government Spending, Human Development Index, East JavaJEL Classification: H72, I31